Guidelines for Reasonable and Appropriate Care in the Emergency Department 2 (GRACE‐2): Low‐risk, recurrent abdominal pain in the emergency department. (11th May 2022) - Broder, Joshua S.; Oliveira J. e Silva, Lucas; Bellolio, Fernanda; Freiermuth, Caroline E.; Griffey, Richard T.; Hooker, Edmond; Jang, Timothy B.; Meltzer, Andrew C.; Mills, Angela M.; Pepper, Joan D.; Prakken, Steven D.; Repplinger, Michael D.; et al.
Abstract: This second Guideline for Reasonable and Appropriate Care in the Emergency Department (GRACE‐2) from the Society for Academic Emergency Medicine is on the topic "low‐risk, recurrent abdominal pain in the emergency department." The multidisciplinary guideline panel applied the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to assess the certainty of evidence and strength of recommendations regarding four priority questions for adult emergency department patients with low‐risk, recurrent, undifferentiated abdominal pain. The intended population includes adults with multiple similar presentations of abdominal signs and symptoms recurring over a period of months or years. The panel reached the following recommendations: (1) if a prior negative computed tomography of the abdomen and pelvis (CTAP) has been performed within 12 months, there is insufficient evidence to accurately identify populations in whom repeat CTAP imaging can be safely avoided or routinely recommended; (2) if CTAP with IV contrast is negative, we suggest against ultrasound unless there is concern for pelvic or biliary pathology; (3) we suggest that screening for depression and/or anxiety may be performed during the ED evaluation; and (4) we suggest an opioid‐minimizing strategy for pain control. EXECUTIVE SUMMARY: The GRACE‐2 writing group developed clinically relevant questions to address the care of adult patients with low‐risk, recurrent, previously undifferentiated abdominal pain in the emergency department (ED). Four patient‐intervention‐comparison‐outcome‐time (PICOT) questions were developed by consensus of the writing group, who performed a systematic review of the literature and then synthesized direct and indirect evidence to formulate recommendations, following GRADE methodology. The writing group found that despite the commonality and relevance of these questions in emergency care, the quantity and quality of evidence were very limited, and even fundamental definitions of the population and outcomes of interest are lacking. Future research opportunities include developing precise and clinically relevant definitions of low‐risk, recurrent, undifferentiated abdominal pain and determining the scope of the existing populations in terms of annual national ED visits for this complaint, costs of care, and patient and provider preferences.